Outcome of Patients with Soft‐Tissue Sarcomas: An Age‐Specific Conditional Survival Analysis. (23rd April 2019) - Bourcier, Kevin; Dinart, Derek; Le Cesne, Axel; Honoré, Charles; Meeus, Pierre; Blay, Jean‐Yves; Michot, Audrey; Le Loarer, François; Italiano, Antoine
Abstract: Background: Soft‐tissue sarcomas (STSs) are a group of rare cancers that can occur at any age. Prognostic outcomes of patients with STS are usually established at the time of the patient's initial disease presentation. Conditional survival affords a dynamic prediction of prognosis for patients surviving a given period after diagnosis. Estimates of conditional survival can provide crucial prognostic information for patients and caregivers, guide subsequent cancer follow‐up schedules, and impact decisions regarding management. This study aims to estimate conditional survival and prognostic factors in patients with STS according to age at diagnosis (≤75 years and ≥75 years). Subjects, Materials, and Methods: A total of 6, 043 patients with nonmetastatic STS at first diagnosis who underwent complete surgical resection (R0 or R1) were assessed. Cox proportional hazards regression was used to establish prognostic factors of conditional metastasis‐free survival and overall survival at 1, 2, and 5 years after diagnosis. Results: Elderly patients have more adverse prognostic features at presentation and tend to receive less aggressive treatment than do younger patients. However, at baseline as well as at each conditional survival time point, the 5‐year estimated probability of metastatic relapse decreases in both young and elderly patients and is almost identical in both groups at 2 years and 5 years after initial diagnosis. Prognostic factors for metastatic relapse and death change as patient survival time increases in both young and elderly patients. Grade, the strongest prognostic factor for metastatic relapse and death at baseline, is no longer predictive of metastatic relapse in patients surviving 5 years after initial diagnosis. Leiomyosarcoma is the histological subtype associated with the highest risk of metastatic relapse and death in young patients surviving 5 years after initial diagnosis. The positive impact on the outcome of peri‐operative treatments tends to decrease and disappears in patients surviving 5 years after initial diagnosis. Conclusion: Conditional survival estimates show clinically relevant variations according to time since first diagnosis in both young and elderly patients with STS. These results can help STS survivors adjust their view of the future and STS care providers plan patient follow‐up. Abstract : Prognostic outcomes of patients with soft‐tissue sarcomas are usually established at the time of the patient's initial disease presentation, based on baseline patient and tumor characteristics. This study focused on conditional survival and prognostic factors in patients according to age at diagnosis.